PENGARUH KARAKTERISTIK PRAKTIK CORPORATE GOVERNANCE TERHADAP PREDIKSI FINANCIAL DISTRESS (Studi Kasus pada Perusahaan Subsektor Pertambangan Batubara yang Terdaftar di BEI Periode Tahun 2009 – 2014) - Anna Quraisy Haq; Brady Rikumahu; Anisah Firli (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
The purpose of this research is to acknowledge the effect of characteristic corporate governance practices on the prediction of financial distress on sub sector coal mining company listed in BEI period 2009-2014. This research can be used as information for companies to know how corporate governance practices could affect the occurrence of a state of financial distress. Independent variables used are institutional ownership, managerial ownership, independent board and audit committee and prediction of financial distress using Altman Z-score as dependent variable. This research is a quantitative study using panel data regression. The population in this study is a sub-sector coal mining company listed on BEI period 2009-2014. The sampling technique in this research is purposive sampling method obtaining 6 companies.The results of research shows that institutional ownership, managerial ownership, independent board and audit committee did not significantly affect the prediction of financial distress. Of the four independent variables, only the institutional ownership that partially has significant impact negatively on the prediction of financial distress.